A revision of the genus Phellopsis LeConte (Coleoptera: Zopheridae) - Foley, Ian A.; Ivie, Michael A. (Zootaxa, 2008)
The world species of Phellopsis LeConte are revised based on the examination of all available material. Phellopsis obcordata (Kirby) and P. porcata (LeConte) are found to be valid vicariant species isolated in old growth boreal forest habitats of eastern and western North America, respectively. Phellopsis robustula Casey and P. montana Casey are placed as junior synonyms of P. porcata NEW SYNONYMIES. On the Asian continent, P. imurai Masumoto is placed in synonymy with P. amurensis (Heyden) NEW SYNONYMY. Phellopsis amurensis (Heyden) now has a documented range that extends from the coastal mountains of Russia’s Primorskii Krai into the Korean peninsula. The other two described species found to be valid are P. suberea Lewis, known only from Japan, and P. chinense (Semenow) from west central China. Phellopsis yulongensis NEW SPECIES is described from the Yunnan Province of western China. Redescriptions of all valid species are provided, with comments on the history of the genus, biology and biogeography of the group. A key and illustrations are provided for the identification of all known Phellopsis species.